Polemik Frase “Duduklah di sebelah kanan-Ku” dalam Mazmur 110:1 - Ryan Renaldy Madunde (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
The book of Psalms, when viewed from a literary point of view, is grouped into a book with a poetic genre, so understanding every word in this book is certainly different when approaching a book with a narrative genre. It is this difficulty that needs to be considered in approaching books with the poetic genre, because this type of literature does not clearly state the background of the situation the author is experiencing when writing the message of God's Word. One of them is in Psalm 110:1 in the phrase